GASL 2017 closing remarks by HE Fekadu Beyene, Ethiopia minister for livestock and fisheries - Beyene, F. (International Livestock Research Institute, 2017)
Closing remarks by Fekadu Beyene, Ethiopia minister for livestock and fisheries at the 7th Multi-stakeholder Partnership (MSP) Meeting of the Global Agenda on Sustainable Livestock, Addis Ababa, Ethiopia.